Case Report: Efficacy and safety of recombinant growth hormone therapy in a girl with Loeys–Dietz syndrome - Kamil Dyrka; Aleksander Jamsheer; Michal Bartecki; Waldemar Bobkowski; Malgorzata Pawelec-Wojtalik; Justyna Rajewska-Tabor; Andzelika Tomaszewska; Justyna Balcerzak; Zuzanna Aniol; Marek Niedziela; Monika Obara-Moszynska (Frontiers in Cardiovascular Medicine)
BackgroundLoeys–Dietz syndrome (LDS) is a clinically and genetically heterogeneous, autosomal dominant aortic aneurysm syndrome with widespread systemic involvement. We present the case of a 16.5-year-old girl with LDS type 2 (LDS2) caused by a heterozygous pathogenic variant, c.1582C>T (p.Arg528Cys), in the transforming growth factor-beta receptor type 2 (TGFBR2) gene who was treated with recombinant growth hormone (rGH) due to coexisting GH deficiency (GHD). This case report (observational study) presents the efficacy of rGH therapy and the safety aspects of this treatment, including aortal imaging follow-up (echocardiography, ECHO). To our knowledge, this is the first investigation of the effects of long-term rGH treatment on aortic dimensions in an LDS patient.Case summaryLDS was recognized in the patient in the 2nd year of life. After the 3rd year of life, growth deceleration was observed. At age 6, GHD was recognized [the maximum GH after stimulation 7.2 ng/ml; insulin-like growth factor-1 (IGF-1), 35 ng/ml; N: 84–447]. At age 6.5 years, rGH was initiated (height standard deviation score, htSDS −2.4), which continued for up to 14.25 years (htSDS-1.4). Her height at 16.5 years was 155 cm. The dose of rGH was 0.025–0.028 mg/kg/day. After the age of 16 months, widening of the aortic root was observed via echocardiography. At nearly 16 years, due to dilated aortic root (Z score +5.95), the girl underwent a plastic operation on the aorta, which had a satisfactory outcome. The patient's current status is stable, but the management of patients with LDS requires multidisciplinary cooperation due to the many coexisting comorbidities.ConclusionsAlthough aortic dilatation occurs in most LDS patients, the possible influence of GH therapy on aortic size must be considered. However, whether IGF-1, the main biochemical marker of GH activity, can be independently associated with increased aortic diameter has not been determined. In addition to its growth-promoting effect, the wide influence of GH on the human body, metabolic status, and muscle strength is also significant. The extremely low IGF-1 level before rGH therapy in the present patient and the strict monitoring of the IGF1/IGFBP3 ratio during rGH administration seem to be safe and beneficial for therapy.